Analisa Perbandingan Penurunan Awal Bendungan Tipe Material Timbunan Urugan Batu dan Urugan Tanah (Studi Kasus Bendungan Digoel-Papua): Comparative Analysis of the Initial Decline of Dam Material Type of Stone Urugan Embankment and Soil Urugan (Digoel Dam-Papua Case Study) - Erlangga Erlangga; Kresno Wikan Sadono; Thomas Triadi Putranto (Universitas Islam 45, 2024)
To create prosperity for the people of Papua Province. The government has made one of the programs, namely the construction of the Digoel Dam in Boven Digoel Regency – Papua. The successful construction and operation of a dam requires a comprehensive evaluation of the design prior to commencement of the construction process. This study aims to analyze the initial settlement that occurred in the Digoel dam type earth fill and rock fill. Initial settlement analysis was carried out using the modulus parameter obtained from the literature. SIGMA/W software has been used to estimate dam crest settlement due to static loading. From the results of the analysis of the initial settlement of the dam with the rock fill and earth fill types, it is accepted that the maximum permissible settlement is 1.59%.